Information Retrieval Technology 6th Asia Information Retrieval Societies Conference, AIRS 2010, Taipei, Taiwan, December 1-3, 2010, Proceedings - Cheng, Pu-Jen; Kan, Min-Yen; Lam, Wai; Nakov, Preslav (Information Systems and Applications, incl. Internet/Web, and HCI, 2010)
The Asia Information Retrieval Societies Conference (AIRS) 2010 was the sixth conference in the AIRS series,aiming to bring together international researchers and developers to exchange new ideas and the latest results in information - trieval. The scope of the conference encompassed the theory and practice of all aspects of information retrieval in text, audio, image, video, and multimedia data. AIRS 2010 continued the conference series that grew from the Information Retrieval with Asian Languages (IRAL) workshop series, started in 1996. It has become a mature venue for information retrieval work, ?nding support from the ACM Special Interest Group on Information Retrieval (SIGIR); the Association for Computational Linguistics and Chinese Language Processing (ACLCLP); ROCLING; and the Information Processing Society of Japan, Special Interest GrouponInformationFundamentals andAccess Technologies(IPSJSIG-IFAT). This year saw a sharp rise in the number of submissions over the previous year. A total of 120 papers were submitted, representing work by academics and practitioners not only from Asia, but also from Australia, Europe, North America, etc. The high quality of the work made it di?cult for the dedicated programcommitteetodecidewhichpaperstofeatureattheconference.Through adouble-blindreviewingprocess,26submissions(21%)wereacceptedasfulloral papers and 31 (25%) were accepted as short posters. The success of this conferencewas only possible with the support of allof the authorswho submitted papers for review, the programcommittee members who constructively assessedthe submissions, and the registered conference delegates. We thank them for their support of this conference, and for their long-term support of this Asian-centric venue for IR research and development.